Prevalence of indirect toxicity effects of aluminium flakes on a shredder‐fungal‐leaf decomposition system. (9th February 2015) - Pacioglu, Octavian; Cornut, Julien; Gessner, Mark O.; Kasprzak, Peter
Summary: Polyaluminium chloride (PAC) addition has been proposed as a technique to precipitate dissolved phosphorus (P) and reduce the internal loading of P in eutrophic hardwater lakes. However, the direct and indirect detrimental effects of PAC on aquatic communities and ecosystem processes are virtually unknown. We determined how PAC may affect a leaf litter–fungus–shredder decomposition system in the littoral habitat of eutrophic hardwater lakes.We hypothesised that PAC will exert little direct toxicity on aquatic organisms at high pH but trigger indirect bottom‐up effects by affecting fungal biomass, leaf litter food quality (Al, N and P contents), trophic transfer and the behaviour and performance of a leaf‐shredding consumer. We tested these hypotheses in a microcosm experiment involving a leaf‐shredding amphipod, Gammarus pulex, offered conditioned aspen leaves as food. We measured concentrations of Al, N, P and organic C in water, leaves and gammarids; fungal biomass associated with leaf litter; gammarid survival, body mass, feeding rate (FR) and N assimilation efficiency; and fine‐particulate organic matter (FPOM) generation in microcosms receiving 0, 2 and 20 g Al flakes per m 2 . Survival rates of G. pulex were similar in all microcosms, suggesting that even the high dose of Al flakes was below lethal levels. However, exposure to Al flakes decreased fungal biomass in leaves, the FR of gammarids, FPOM production and N assimilation efficiency. The C/N and C/P ratios of both leaves and gammarids also decreased in microcosms receiving Al flakes, supporting the hypothesis that stoichiometric imbalances between food and consumers were altered by exposure to Al flakes. These results point to the importance of indirect effects of PAC on lake communities and ecosystems beyond direct toxicity on invertebrates. Although not all those effects are necessarily undesirable, their numbers, interdependencies and potential to act in concert suggest they need to be considered in ecotoxicological assessments.